Experimental assessment of different strengthening techniques for opening in reinforced concrete beams - Fatma Agag; Seleem S. E. Ahmad; Hossam El-Din M. Sallam (Fracture and Structural Integrity)
The present experimental study includes testing thirteen reinforced concrete beams with openings at different locations to investigate the efficiency of strengthening such openings. Different strengthening techniques around the opening after and before casting include diagonal bars, upper and lower steel, and carbon fiber reinforced polymers (CFRP), were examined. All beams were made from 30 MPa compressive strength and tested under four-point loading.  The cross section of the beams is 400 mm depth x 160 mm width and beam length 2400 mm. The dimensions of the opening are 200 mm x 200 mm. The stiffness, deflection, failure load, and failure mode of the strengthened beams were discussed. Experimental results showed that the beams strengthened with upper and lower steel around opening at mid-span increase the load-carrying capacity by 16.59%. However, beams strengthened by CFRP sheets around the opening in the shear zone increase the load carrying capacity by 47.7% compared to opened beam.